2018
DOI: 10.1159/000490466
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Index in Pediatric Pilocytic Astrocytoma by Region of Origin and Prediction of Clinical Behavior

Abstract: Background/Aims: Pilocytic astrocytomas are common pediatric tumors. Molecular profiles vary with location of origin. Comparisons of proliferation have not been reported. We sought to identify differences in growth by region and whether these predict clinical behavior. Methods: A retrospective review of all patients undergoing surgery for a pilocytic astrocytoma at Children’s Hospital LA from 2003 to 2015 was completed. Tumor location, determined by imaging, was stratified into infratentorial, supratentorial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In 2003, Bowers et al reported of a study including 118 Pilocytic astrocytoma (PA) patients, showing a shortened PFS in patients with tumors bearing a MIB-1 LI > 2%. This data is in line with four subsequent studies on PAs including 35–80 cases, reporting a significant negative correlation of KI-67/MIB-1 LI and PFS (Fisher et al 2002 ; Dorward et al 2010 ; Margraf et al 2011 ; Tu et al 2018 ). In contrast, Horbinski et al ( 2010 ) published a case series including 118 patients, showing no correlation of MIB-1 LI and adverse treatment outcome including recurrence, progression, metastatic spread or death.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…In 2003, Bowers et al reported of a study including 118 Pilocytic astrocytoma (PA) patients, showing a shortened PFS in patients with tumors bearing a MIB-1 LI > 2%. This data is in line with four subsequent studies on PAs including 35–80 cases, reporting a significant negative correlation of KI-67/MIB-1 LI and PFS (Fisher et al 2002 ; Dorward et al 2010 ; Margraf et al 2011 ; Tu et al 2018 ). In contrast, Horbinski et al ( 2010 ) published a case series including 118 patients, showing no correlation of MIB-1 LI and adverse treatment outcome including recurrence, progression, metastatic spread or death.…”
Section: Introductionsupporting
confidence: 89%
“…While nowadays amending an integral part to histopathological routine diagnostics in CNS tumors, assessment of MIB-1 LI has previously shown to contribute to differentiation of the degree of malignancy in tumors of the central nervous system, while a significant correlation to WHO grade in human glioma has been reported (Matsumoto et al 1998 ; Pollack et al 2002 ; Skjulsvik et al 2014 ; Hsu et al 1997 ; Krishnan et al 2019 ). However, as compared to distinct solid CNS and non-CNS malignancies, previous analyses of smaller PLGG cohorts addressing the prognostic value of KI-67/MIB-1 LI in PLGG, many of them from the pre-molecular era, draw conflicting conclusions and necessitate further assessment (Bowers et al 2002 , 2003 ; Fisher et al 2002 ; Dorward et al 2010 ; Margraf et al 2011 ; Tu et al 2018 ; Horbinski et al 2010 ; Cherlow et al 2019 ; Cler et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 c). The glioma tumor areas exhibited low proliferative indices (4–6% Ki67 + cells), within the upper range of proliferation rates seen in pediatric PAs [ 64 ], whereas the embryonal-like areas exhibited slightly higher proliferative rates (8–15% Ki67 + cells) (Fig. 2 a, c).…”
Section: Resultsmentioning
confidence: 81%
“…Histopathological features such as vascular hyalinization and proliferation, calcifications, and necrosis have been associated with reduced PFS; 21,22 however, these associations are not consistently observed across studies. 7 The Ki-67 proliferative index has been associated with reduced PFS, 15,23,24 but this finding has also been inconsistent. 22 Increased cellularity has been observed in recurrent tumors, 25 but a causal relationship between cellularity in initial tumors and PFS has not been established.…”
mentioning
confidence: 99%